Moral distress among nurse leaders: A qualitative systematic review - Miller, Preston H (Nursing ethics, 2023)
Moral distress (MD) is well-documented within the nursing literature and occurs when constraints prevent a correct course of action from being implemented. The measured frequency of MD has increased among nurses over recent years, especially since the COVID-19 Pandemic. MD is less understood among nurse leaders than other populations of nurses. A qualitative systematic review was conducted with the aim to synthesize the experiences of MD among nurse leaders. This review involved a search of three databases (Medline, CINAHL, and APA PsychINFO) which resulted in the retrieval of 303 articles. PRISMA review criteria guided authors during the article review and selection process. Following the review, six articles were identified meeting review criteria and quality was assessed using the Critical Appraisal Skills Programme (CASP) Checklist for qualitative studies. No ethical review was required for this systematic review. The six studies included in this review originated from the United States, Brazil, Turkey, and Iran. Leadership roles ranged from unit-based leadership to executive leadership. Assigned quality scores based upon CASP criteria ranged from 6 to 9 (moderate to high quality). Three analytical themes emerged from the synthesis: (1) moral distress is consuming; (2) constrained by the system; and (3) adapt to overcome. The unique contributors of MD among nurse leaders include the leadership role itself and challenges navigating moral situations as they arise. The nurse leader perspective should be considered in the development of future MD interventions.